A study on Malaysian legal framework and risk management: design works - Ahmad Rashid1, Zul Zakiyuddin; Adnan, Hamimah (2008)
The construction industry is subject to more risk and uncertainty than many other industries. Construction projects are associated with various aspect of risks, be it risks associated with the feasibility stage, design stage, construction stage and post construction stage. This paper is meant to address two main concerns. The first objective is to identify the understanding of Malaysian architects on risks related to design and the management of such risks. Secondly, this paper will look into the architects’ apprehension on laws corresponding to the notion of proper risk management framework. A set of questionnaire was sent to the respondents; the PAM registered architects, with the view of securing data from the respondents on risks related to design, risk management and the PAM standard form of building contract and the general law on design risk management. The findings will be analyzed in contrast with the theoretical framework derived from the literature reviews on design related risks, risk management and the law. Based on the replies received, the respondents, irrespective of their years of experience and frequency in dealing with the PAM 1998 Form of Building Contract (PAM 1998) agreed that there are risks involved with design works. These risks must be properly addressed to ensure the success of the project. In addition to that, most of the respondents agreed that the risks originated from the same sources. The respondents also agreed on the scope of their duty to be fully scrutinized in order to avoid risks. However, while most agreed on the basic element of risk management, mix views were evidenced on risk response method. With reference to the legal framework, most respondent understand the laws regulating their duties and generally accept the law as an important risk management tools. Nevertheless, respondents misconception of the law as well as the insufficiency of the legal provisions itself pertaining to architects and design works may defeated the whole purpose of establishing a proper framework for risk management.